TINJAUAN YURIDIS TERHADAP KLAUSULA DALAM PERJANJIAN WARALABA YANG DAPAT MENIMBULKAN PRAKTIK MONOPOLI - Wulan Purwanti, Ni Luh Putu; Eka Wisanjaya, I Gede Pasek (Kertha Semaya : Journal Ilmu Hukum, 2014)
This paper shall be titled “Judicial Review Against The Clause In The FranchiseAgreement That Can Lead To Monopolistic Practices”. This paper is written based on aclause in the franchise agreement that could potentially lead to monopolistic practicesgiven the franchise excluded from The Act Number 5 Year 1999 Concerning ProhibitionOf Monopolistic Practices And Unfair Business Competition. As for the purpose of thisdiscussion is to understand the franchise agreement and how a clause in the franchiseagreement may lead to monopolistic practices. This paper is a normative legal researchusing the Statute Approach. Franchise agreement are exempt from The Act Number 5 Year1999 Concerning Prohibition Of Monopolistic Practices And Unfair Business Competitionto maintain identity, reputation and intellectual property right of the franchise. Clause inthe franchise agreement that could potentially lead to monopolistic practices are notincluded in the exceptions in Article 50 letter b The Act Number 5 Year 1999 On TheProhibition Of Monopolistic Practices And Unfair Business Competition.
Keywords: Clause, Franchise Agreement, Monopolistic Practices.